Structural, Physicochemical, and Digestion Properties of Sweetpotato Starches - Alayouni, R.; Muzhingi, T.; Nakitto, M.; Baride, A.; Yao, T.; Janaswamy, S. (Elsevier, 2025)
Sweetpotato starch has significant nutritional value. However, there is considerable variability in starch characteristics among different sweetpotato cultivars, necessitating a deeper understanding of the inherent varietal differences. This study compares the structural and physicochemical properties of starches from seven sweetpotato varieties: NASPOT8, NASPOT10 O, NASPOT11, NASPOT12 O, NASPOT13 O, Kakamega, and Ejumula, cultivated in Uganda. The results suggest that sweetpotato starch granules are irregularly elliptical. The amylose content ranges from 20.87% to 35.40%, with low starch damage of 0.19% to 0.53%. The peak viscosity, final viscosity, breakdown viscosity, and setback viscosity vary from 9973 cp to 19258 cp, 2190 cp to 5901 cp, 6791 cp to 14195 cp, and 272 cp to 1501 cp, respectively. X-ray diffraction analysis reveals Cc-type starch with a relative crystallinity of 11.76% to 15.34%. The RDS, SDS, and RS amounts vary significantly (p<0.05) from 70.20% to 79%, 9.42% to 16.02%, and 7.72% to 15.48%, respectively. NASPOT8 has unique features among the seven varieties, including reduced pasting viscosity, higher gelatinization temperature, and lower digestibility. The findings provide valuable insights into using sweetpotato varieties grown in Uganda for various food and non-food applications.